Assessing Palliative and End-of-Life Educational Needs of Pediatric Health Care Professionals: Results of a Statewide Survey. Issue 5 (October 2017) - O'Shea, Eileen R.; Lavallee, Matthew; Doyle, Elizabeth A.; Moss, Kerry
Abstract : Children with serious, complex medical or life-threatening conditions and their families often fail to receive effective, consistent, timely, and competent care that meets their physical, emotional, and spiritual needs. Enhancing both basic education and advanced skills in pediatric palliative and end-of-life care education is recommended so that health care providers will enter practice with some form of formal preparation. In this quantitative descriptive study, we used the End-of-Life Professional Caregiver Survey to assess unmet palliative and end-of-life educational needs of pediatric health care providers in the state of Connecticut. Participants who received palliative care education in the past 5 years had higher mean scores on all 3 factors of the End-of-Life Professional Caregiver Survey, which may reflect the evolvement and depth of current pediatric palliative care education. Future palliative educational programs for pediatric providers in Connecticut should include sharing pediatric palliative care principles and national guidelines, describing services provided by pediatric hospice and timing of referral, developing systems to ensure continuity of care crossing all settings, addressing request for assisted suicide, meeting needs of staff and providers caring for the dying child (self-care), and describing cultural and ethical values specific to diverse populations in Connecticut.